2020
DOI: 10.1002/jum.15334
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Ultrasound Elastography and Serologic Fibrosis Indices for Evaluation of Hepatic Involvement in Wilson Disease

Abstract: Objectives-To investigate the diagnostic value of transient elastography (TE), 2-dimensional (2D) shear wave elastography (SWE), and the serologic fibrosis indices aspartate transaminase-to-platelet ratio index (APRI) and Fibrosis-4 (FIB-4) score for Wilson disease (WD). Methods-We retrospectively identified patients with a diagnosis of WD who underwent TE and 2D SWE on the same day. Their APRI and FIB-4 scores were calculated. Hepatic involvement was classified into 5 clinical categories (I-V) based on the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Transient elastography (TE) is an extended imaging technique, based on the measurement of tissue stiffness by ultrasounds, useful to ascertain the degree of hepatic fibrosis in several liver diseases, particularly in hepatitis C. Few studies have evaluated its performance as well as that of other non-invasive scores based on classical serum markers such as FIB-4 or APRI (AST-to-Platelet Ratio) in WD. TE solely or in combination with FIB-4 or APRI scores seems to provide an adequate positive predictive value (PPV) for diagnosis of advanced fibrosis and cirrhosis in WD patients [ 53 , 54 ]. Of note, the optimal threshold TE values reported in WD patients to discriminate cirrhosis (≥9.9 kpas) are notably lower than those for other liver diseases [ 53 , 55 , 56 ].…”
Section: Clinical Picture Of Wilson’s Diseasementioning
confidence: 99%
“…Transient elastography (TE) is an extended imaging technique, based on the measurement of tissue stiffness by ultrasounds, useful to ascertain the degree of hepatic fibrosis in several liver diseases, particularly in hepatitis C. Few studies have evaluated its performance as well as that of other non-invasive scores based on classical serum markers such as FIB-4 or APRI (AST-to-Platelet Ratio) in WD. TE solely or in combination with FIB-4 or APRI scores seems to provide an adequate positive predictive value (PPV) for diagnosis of advanced fibrosis and cirrhosis in WD patients [ 53 , 54 ]. Of note, the optimal threshold TE values reported in WD patients to discriminate cirrhosis (≥9.9 kpas) are notably lower than those for other liver diseases [ 53 , 55 , 56 ].…”
Section: Clinical Picture Of Wilson’s Diseasementioning
confidence: 99%
“…Strong agreement between 2D-SWE and TE in the evaluation of liver fibrosis has been previously studied in a few adult cohorts ( 31 33 ) and two pediatric studies ( 9 , 21 ). Herein, we found a moderate concordance for liver fibrosis stages between 2D-SWE and TE, which could be explained by the technical differences between these methods ( 34 ) that may hinder direct comparison.…”
Section: Discussionmentioning
confidence: 92%
“…In children, liver fibrosis assessment in chronic liver diseases using 2D-SWE compared with liver histology showed good-to-moderate correlations with fibrosis stage [i.e., rho = 0.83 ( 3 ) and rho = 0.43 ( 27 )]. Although many authors have described use of 2D-SWE and TE in specific pediatric liver diseases such as biliary atresia ( 5 , 28 ), obesity ( 7 ), and Wilson disease ( 9 ), only one previous study reported a comparison of these two methods in various chronic liver diseases ( 21 ) (see Supplementary Table ). The moderate correlation herein between 2D-SWE and TE in children 6 years or younger could be a result of having a larger number of patients with no or low liver fibrosis in this age group and/or the narrower range of value for stages < F2 compared with those > F3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study investigated the laboratory indicators but only FIB-4 and APRI were included for analyses. FIB-4 and APRI are commonly used for monitoring liver brosis in chronic hepatitis B and C as well as WD [21]. Whether the prediction e cacy of 2D-SWE will be affected when more laboratory indicators are added in the research needs further investigation.…”
Section: Discussionmentioning
confidence: 99%